REVITALISASI PEKARANGAN LANSKAP PERDESAAN SEBAGAI PENYEDIA JASA LANSKAP UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Kaswanto, Regan Leonardus; Filqisthi, Tataq Aisyah; Choliq, M. Bagus Suryono (Jurnal Lanskap Indonesia, 2017)
A robust management for Indonesian typical home garden or usually called as “pekarangan” is needed to resolve environmental problems in rural landscape, particularly in developing countries. A well planned and managed landscape practices may suppress social economical and ecological development in rural marginal society. Therefore by revitalizing pekarangan systems, marginal communities would have the possibility to advance their asset of landscape services through plant biodiversity (H’) and carbon stock (C) inside pekarangan. The aim of this research is to develop basic landscape service of plant biodiversity and carbon stock, to analyze the correlation between both of them, and to arrange recommendation for revitalizing pekarangan. The results show that pekarangan has diverse plant biodiversity (0.77-3.57) and diverse carbon stock (0.13-136.20 Mg/ha. However plant diversity in mid to high scale (H’ > 1.00) reach 98.95% and high carbon stock (C > 10.00 Mg/ha) reach 45.83%. And there is positive correlation among both of them (Y=0.0099X + 2.0299). Those landscape services provided by pekarangan account to mimic forestry landscape.